Principles of optimization theory - Bector, C R (Alpha Science International, 2005)
This text provides the fundamental principles of optimization theory blended in a judicious way with current research. Using the powerful language of convex analysis it helps the reader to probe into such advanced topics like Nonsmooth Optimization and Conjugate Duality. The now traditional area of differentiable optimization has been revisited and many new insights have been provided by presenting very recent research in this area